The Effect of Money Ethics and Machiavellianism on Tax Compliance With the Moderating Role of Religiosity - Sasmita; Lince Bulutoding; Nur Rahmah Sari (Academic Bright Collaboration, 2025)
This study aims to analyze the influence of money ethics and machiavellianism on tax compliance, with religiosity as a moderating variable, among individual taxpayers at the Makassar Selatan Primary Tax Office. A quantitative approach was employed using primary data collected through questionnaires and analyzed with multiple linear regression and Moderating Regression Analysis (MRA). The results indicate that money ethics and machiavellianism have a negative effect on tax compliance, while religiosity does not moderate the relationship. The novelty of this study lies in integrating psychological aspects of money ethics and machiavellianism, which have rarely been examined together, thereby offering a new perspective on understanding individual tax compliance behavior in Indonesia.